(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
Undergraduate Medical Education Board, National Medical Commission has released the academic calendar for MBBS batch 2022-23 via letter no U. 11026/02/2022- UGMEB dated 12th October, 2022. Academic calendar provides an overview of the entire MBBS course and timeline for teaching, examination and other academic activities. In this calendar, electives were reduced from total 2 months to 1 month (15 days for pre/para clinical branches and 15 days for clinical branches). Yoga, family adoption program through village outreach will be continued as 2021-22 batch. Letter said that remaining rules and regulations should be as per GMER (Graduate Medical Education Regulation) 1997 which is confusing because latest Regulations on Graduate Medical Education (Amendment), 2019 were already released on 4th November, 2019. Date of starting the first MBBS is 15th November, 2022 but no mention of the foundation course. Subjects of ENT and Ophthalmology were shifted to IIIrd part 2 and IIIrd part 1 have only Forensic Medicine and Toxicology along with Community Medicine. This is a major change pertaining to the future NExT examination. As the document is very short, many questions remained unanswered or created confusions in the minds of faculties of various subjects including Forensic Medicine and Toxicology. On 7th December, 2022, NMC has released updated phase wise academic calendar for 2022-23 MBBS batch to resolve various queries. On 28th December, 2022, National Medical Commission has released proposed draft regulations related to National Exit Test (NExT) for seeking comments of the stakeholders. In the present state, one has to wait for final directions from NMC for clarity because of continuous improvement in various guidelines related to medical education.